SANGICOCCUS SP., A NEW RECORD OF PEST DEVASTATING COCONUT PALMS IN PALAWAN, PHILIPPINES - E.P. Pacumbaba; J.C. Orense; M.B. Zipagan; M.L.R. Imperial (International Coconut Community, 2000)
Sangicoccus sp. nr. truncatispinus (Reyne) (Eriococcidae: Homoptera) is recorded for the first time as a major pest of coconut palms in the Philippines. It is also the first record among the coconut growing areas in the world. It sucks the plant sap resulting to chlorosis of leaves. Furthermore, honeydew droplets exuded by the pest accumulated on upper leaf surfaces become substrate for sootymolds. The severe infestation observed in late 1980’s already spread to 6 out of 8 municipalities of the southern second district of Palawan. Presently, crop losses are estimated to reach 53% of the nut yield. The prevailing easterly and westerly wind directions of 1-5 m/sec coupled with the dense manner of planting enabled first instar nymphs (crawlers) to spread to other palms. The long dry spell also favored the proliferation of Sangicoccus sp.bv. Controlling the spread and outbreak of this pest seems to be difficult as it thrives on eleven alternate hosts. Ant attendance contributed to dispersal and protection from natural enemies. Moreover, field population of ten predatory species remained minimal. Possible strategies for its control are presented.